Techno-economic evaluation of co-firing biomass gas with natural gas in existing NGCC plants with and without CO2 capture. (June 2016) - Khorshidi, Zakieh; Florin, Nick H.; Ho, Minh T.; Wiley, Dianne E.
Highlights: The impact of biomass gas quantity and quality on the performance and economics of co-firing at a NGCC power plant is assessed, including the impact of capture. Three co-firing levels (5%, 20%, 40%) and three biomass gasification technologies (atmospheric air-blown gasification, pressurized oxygen-blown gasification and atmospheric indirectly heated gasification) were evaluated. The results show that the type of the gasification technology did not have a major impact on plant efficiency, emission intensity or cost of electricity of co-firing. Different economic conditions were assessed to evaluate the conditions were required to make co-firing cost competitive. Modest incentives (carbon price > 27 $/t CO2 and REC > 10 $/MWh or combination of both at lower levels) were found to be sufficient to encourage co-firing. Abstract: Natural gas combined cycle (NGCC) power plants have emission intensities a half to a third that of current coal-fired power plants. To meet more stringent emission targets, it is essential to reduce the emissions of these plants to an even lower level. Co-firing gasified biomass with natural gas (NG) reduces the plant emissions while allowing continued use of existing assets. If CO2 capture and storage are also applied, negative emissions may result which could provide additional CO2 credits to reduce the overall cost of decarbonising electricity generation. This paper investigates the impact of biomass gas quantity and quality on the performance and economics of a 547 MWe NGCC plant retrofitted with biomass gas co-firing. The analysis considers co-firing with and without CO2 capture. Three co-firing levels (5%, 20%, 40%) and three biomass gasification technologies (atmospheric air-blown gasification, pressurized oxygen-blown gasification and atmospheric indirectly heated gasification) are evaluated. Compared to the baseline NGCC power plant, at low co-firing levels, the type of gasification technology does not significantly affect the overall thermal efficiency, CO2 emission intensity or cost of electricity (COE). However, at higher levels of co-firing, the overall thermal efficiency increases by up to 2.5% LHV for the atmospheric air-blown gasifier but decreases by about 0.4% LHV for the pressurized oxygen-blown gasification and 2.5% for atmospheric indirectly heated gasification technologies. The CO2 emission intensity also changes by up to 0.16–0.18 t/MWh at co-firing levels of 40% for all three gasification technologies, while the COE increases by 0.12–0.18 $/MWh. The analysis also shows that the increase in the fuel flow rate is more significant for BGs with lower heating values. The increase in the fuel flow rate can increase the topping cycle efficiency but requires more modifications to the gas turbine. Thus, co-firing BGs with lower heating value might be less suited to retrofit scenarios. By applying capture to co-firing plants, negative emissions are achieved at medium and high co-firing levels with 7–18% increase in the cost of electricity relative to NGCC with capture. An evaluation of the effect of incentive schemes shows that relatively modest incentives (carbon price > 27 $/t CO2 and REC > 10 $/MWh or combination of both at lower levels) are required to make co-firing cost competitive, while higher incentives are required for co-firing coupled with capture (carbon price > 46 $/t CO2 and REC > 78 $/MWh or combination of both at lower levels). As the co-firing level increases, lower incentives are needed to achieve economic feasibility.